FEM method structural analysis of pressure hull by using hyper mesh - Balaji, V.; Ravi, S.; Naveen Chandran, P. (International Journal of Engineering and Technology, 2017)
Pressure hulls are the central load bearing structures of naval submarines, and AUVs ( autonomous underwater vehicles)..Â A pressure hull is a structure that is designed to resist the compressive forces related with hydrostatic pressure. The most coherent geometries for resisting these compressive forces are annular cross-sections, and thus, pressure hulls are typically composed of a combination of cones and ring-stiffened cylinders, with torispherical domes or sphericalÂ at either end. These shells are subject to an external pressure of 65 Bar due to the difference between outside and inside pressure.In the Â current paper, 3-D Modelling are carried out as per ASME codes to endure the pressure of 65 Bar. At length to thickness ratio of the pressure hull is very large, both 3D shell and 3D solid FEA models were developed and analyzed using Ansys Simulation. The 3D modeling of the assembly has used UNIGRAPHICS software and Finite element analysis is done using ANSYS-Hyper Mesh software.